Hydrogeologic Characteristics and Groundwater Potentiality of Lower Aquifer of Singair Upazila, Manikganj District, Bangladesh - Islam, Mazeda; Bashar, Khairul; Ahmed, Nasir; Rasul, Md Golam; Hossain, Sahadat; Sarker, Md Mizanur Rahman (Journal of Bangladesh Academy of Sciences, 2018)
The study area is located in the central part of Bangladesh. The aims of this study were to explain the hydrogeological characteristics of aquifers and evaluate the groundwater potentiality. The borehole logs revealed three types of zones: upper aquitard (low permeability clays, silty clays & silts), upper aquifer (very fine sand to fine sand) and lower aquifer (medium to coarse sands and gravels). Both aquifer waters are mainly Ca-Mg-HCO3 type. Except arsenic (As), most of the ions of both aquifer waters are within the limit of drinking standard of WHO (2004) and Bangladesh (DoE, 1997). Arsenic concentrations of upper aquifer exceed both the WHO (10 μg/l) and Bangladesh standard (50 μg/l) and for lower aquifer exceed only WHO standard. Waters of both aquifers in north western and central part of the study area show high arsenic concentration due to lack of continuous impermeable layer between them as revealed from borelog data. Water quality index map also indicates that north western and central part is not suitable for groundwater development because of inferior quality. The average δ18O values for upper and lower aquifer waters are isotopically enriched compared to river water ( 10.08‰). Similar isotopic composition of upper ( 4.77‰) and lower aquifer waters ( 5.50‰) indicates both waters were mixed in the past and mixing may be continued in the future. The mixing may be preferentially from the upper aquifer to lower aquifer because of water abstraction, lack of impermeable layer and high permeability of the upper aquifer etc. Therefore, the potentiality of the lower aquifer may not be suitable for large-scale groundwater development project without any mitigation measure. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 25-40, 2018